Carga mental de trabalho e o apoio social em trabalhadores da atenção primária a saúde - Silva, Marculina da (2023)
Mental workload (MWL) and social support are psychosocial aspects that may positively or negatively influence workers’ health and well-being in their daily work. For this reason, it is important to emphasize these constructs with an approach of work-health relationship. The present study aimed to analyze the relationship between mental workload and social support in primary health care workers. This is a cross-sectional survey carried out with primary health care (PHC) workers, belonging to the units of the 4th Regional Health Coordination and the city of Ijuí. Data collection took place online from July 2021 to April 2022 using the following instruments: questionnaire with sociodemographic, work and health profile questions; Job Stress Scale (JSS) and Subjective Mental Workload Scale (ESCAM). Descriptive statistics analysis was performed using location measurements such as mean, median, minimum and maximum, dispersion, standard deviation and interquartile range, based on the KolmogorovSmirnov test. Spearman’s correlation, chi-square or Fischer’s exact test were used, considering statistical significance when the p value was less than or equal to 0.05, and Cronbach’s alpha. Ethical precepts of research involving human beings were respected. As a result, the participants were predominantly female (89.0%), with a partner (80.1%), and children (74.3%), with a median age of 43.00 years. Post-graduate degrees prevailed (35.6%) as the highest levels of education and the largest number of workers were community health agents (CHAs) (33.5%). There was a prevalence of 48.7% of health professionals with adequate overall mental workload. As for dimensions, 42.9% of workers had mental underload in the organization of time. As for social support, 57.6% of professionals had low support. It was evident that workers with high social support had an adequate global mental workload (p = 0.022). The variable health consequences had a low and negative correlation with social support (r = -0.232; p = 0.001). Social support also showed a low and negative correlation with time organization and Global Mental workload (GMWL) (r = -0.162; p = 0.025, and r = -0.192; p = 0.008, respectively). There was a low negative correlation between GMWL and the age variable (r = -0.207; p = 0.004). Social support had a statistically significant association with health consequences (p = 0.006). Furthermore, there was an association between social support and time organization (p = 0.019). It was identified that workers who have leisure time have adequate GMWL (p = 0.000). Position and job satisfaction were also associated with CMTG (p = 0.001 and p = 0.028, respectively). There was an association between greater academic degree and social support (p = 0.012). Furthermore, job satisfaction was associated with social support, that is, dissatisfied/neutral workers had low social support (p = 0.000). Thus, it is concluded that, despite the adequate mental workload, the dimension time organization showed an imbalance in mental workload. Thus, it is advisable that the working conditions be redesigned so as to favor of the worker’s health. Still, due to the low social support found in this study, which can generate a conflicting environment and negatively impact the quality of life and wellbeing at work, it is important to propose intervention strategies to promote higher support and safety in the occupational space.